(untitled) (Nexo Revista Científica, 2021)
The presented article reviews the history of drilling the deepest well in the world, located in the northeastern part of the Early Proterozoic Pechenga structure (Kola Peninsula). In 1990, the Kola Superdeep Borehole (SG-3) reached a record depth of 12,262 m. SG-3 fully completed all the assigned tasks, both in technical and scientific terms. The 4024 linear meters of core were extracted, including drill samples from a record depth. Overall, a whole complex of logging geophysical works with a total length of 400 thousand km was performed through the use of 25 methods. This allowed obtaining the latest information on the structure and composition of the deep horizons of the earth’s crust, which qualitatively changed the data of previous deep seismic studies. Also, the emerging data on the chemical and mineral composition, as well as the research of physical properties of deep rocks, proved the presence of ore mineralization and metal-bearing hydrothermal systems. SG-3 at its depth uncovered new ore bodies of copper-nickel ores; six types of ore mineralization have been identified throughout the section of the borehole. High permeability for fluids and hydrothermal solutions of deep zones of the earth’s crust was established, which is associated with increased porosity and rocks fracturing. It was also proved that the earliest Precambrian metasedimentary rocks were formed with the active participation of biological processes. The presented analysis of the deep-hole drilling experience allows the author to confirm the status of SG-3 as the deepest artificial point on Earth.